RETHINKING MEASUREMENT IN EDUCATION: A CRITICAL EXAMINATION OF PROPERTIES IN EDUCATIONAL SCALES - Oku, Kingsley (African Journal of Social and Behavioural Sciences, 2026)
Educational measurement is essential to teaching, learning, assessment, curriculum evaluation, and educational decision-making. As educational systems increasingly rely on quantitative evidence to guide policy and practice, concerns have emerged regarding the quality and psychometric adequacy of educational scales used to measure latent constructs such as achievement, depression, locus of control, motivation, self-efficacy, engagement, attitude, and learning outcomes. Traditional approaches to measurement often emphasize score generation while overlooking critical scale properties that determine the trustworthiness and interpretability of results. This position paper advocates a rethinking of educational measurement with a stronger emphasis on validity, reliability, factor structure, measurement invariance, fairness, and technological responsiveness. The paper argues that educational scales should be evaluated not merely by their ability to produce scores but by the extent to which those scores accurately, consistently, and equitably represent the intended constructs. Implications for educational research, assessment practices, and curriculum evaluation are discussed.